Recent advances on metal nitride materials as emerging electrochemical sensors: A mini review - Shafiee, Saiful 'Arifin; Perry, Samuel; Hamzah, Hairul Hisham; Mahat, Mohd Muzamir; Al-Lolage, Firas A.; Ramli, Muhammad Zahir (Elsevier, 2020)
Metal nitride materials are garnering interest in many fields including electrochemistry, although they are still at an early stage of investigation and underexplored. This mini review provides insights on the latest advancements in the field of electroanalytical chemistry based on metal nitride materials, specifically focusing on the best performing transition metal nitride sensors published between 2017 and 2020 for important targets such as glucose, hydrogen peroxide and dissolved oxygen. Nickel cobalt nitride electrodes demonstrate electrocatalytic behaviours toward glucose oxidation and hydrogen peroxide reduction processes. Meanwhile, zirconium nitride electrodes could replace platinum/carbon electrodes for oxygen reduction reaction. This article also introduces solid molybdenum nitride microdisk electrodes, which can easily be prepared and maintained and show diffusion-control voltammetric responses for the complex peroxodisulfate reduction reaction. This mini review will benefit researchers who would like to delve into the potential of metal nitride electrodes as electrochemical sensors